'Are We Ready?': Belgium and the Entente's Military Planning for a War Against Germany, 1906–1914. Issue 6 (2nd November 2019) - Draper, Mario
Abstract: While historians have consistently focused on the development of German, French, and British planning in the years preceding the Great War, few have truly acknowledged neutral Belgium's role in defining the strategic paradigm of 1914. Belgium held the strategic key to the opening salvos of a future Franco-German war, and each of its Guarantors were determined to obtain the initiative. While German planners were prepared to seize it by force, the Entente (particularly Britain), remained wary of its obligations. Instead, Britain sought to determine Belgian intentions and capabilities through secret and unbinding staff conversations in 1906 and 1912. The former proved useful in establishing a framework for co-operation but ultimately came to nothing. By the time they were resumed in 1912, Anglo-Belgian diplomatic relations had soured, while Belgium's military reforms and its emergence as a colonial power gave it a renewed sense of confidence. Belgian officials were determined to retain the kingdom's agency in the formulation of its defence policy and resented Entente suggestions of pre-emptive action. Neutrality was subordinated to independence, which itself could not be guaranteed were Belgium to conclude even the loosest of military accords. Consequently, Entente plans were forced surrender the strategic initiative to the Germans.